Molecular approach to the characterization of lipase encoding genes from Moraxella sp. SBE01 - Siti Soleha; Syarifah Syarifah; Tito Nurseha; Awalul Fatiqin; Endah Retnaningrum; Yitro Serang (Universitas Nahdlatul Ulama Surabaya, 2024)
Lipase from Moraxella sp. SBE01 is an expression of the gene encoding lipase. Detection and characterization of the Moraxella sp. SBE01 lipase coding gene is necessary for large-scale lipase production through genetic engineering. This study aimed to observe the molecular weight, amino acid sequence, length, and conserved amino acids in the DNA encoding the lipase gene, with the goal of identifying and characterizing the lipase-coding gene from Moraxella sp. SBE01. The primer design process was conducted to amplify the lipase gene from Moraxella sp. SBE01 using specialized software for sequence alignment and phylogenetic analysis. Amplification was carried out using PCR with the designed primer, forward primer (GTC ATG ATG TAC TTC CAY GGN GGN GG), reverse primer (GGT TGC CGC CGG CDS WRT CNC C). PCR was carried out under pre-denatured conditions at 95°C (3 minutes), followed by 30 cycles of denaturation at 95°C, annealing at 66°C (30 seconds), 70°C elongations (1 minute) and final elongation of 70°C (10 minutes). The PCR results were electrophoresed using 1% agarose gel with a 1 kb DNA marker. The PCR results were sequenced and analyzed for gene and amino acid sequences and the type of lipase expressed. Sequencing resulted in 387 bp of the nucleotide sequence. The gene and amino acid sequences from Moraxella sp. SBE01 had high homology with the gene and amino acid sequences from Moraxella sp. strain TA144. The lipase gene encodes a protein consisting of 129 amino acids and contains a conserved HGG (His-Gly-Gly) motif, which is characteristic of lipases in family IV, also known as the hormone-sensitive lipase (HSL) family. This conserved sequence suggests that the lipase shares structural and functional similarities with other enzymes in the HSL family, playing a key role in lipid metabolism.